Corporate social responsibility business philosophy in global times - Pasag, Engelbert Calimlim (International Journal of Philosophy, 2016)
Today’s larger corporations engage in Corporate Social Responsibility (CSR) for myriad reasons. Anchored in philosophical treatises, the paper discusses the different facets of CSR. It presents some CSR practices of local and multinational corporations and how these practices take care of the triple bottom line and maintain good corporate image. It also presents drawbacks to business ethics.The last part of the paper presents some challenges that CSR is facing. This paper argues that businesses should see CSR as a responsibility of creating a better life for the larger society as it creates a better life for its stakeholders.